Doppler Sonography of Umbilical Artery throughout Pregnancy in Sheep - Kumar, Sandeep; Chandolia, Ramesh Kumar; Pandey, Anand Kumar; Pradeep; Hitesh; Singh, Gyan; Saini, Gitesh (The Indian Journal of Animal Reproduction, 2022)
The Color Doppler study on 6 pregnant ewes was conducted twice a week from Days 20 to 60 post-mating, then at weekly intervals till the end of experiment by the transrectal and transabdominal ultrasonography. In order to evaluate the waveforms and velocity blood flow patterns, peak systolic velocity (PSV), end diastolic velocity (EDV), pulsatility index (PI) and resistive index (RI), were measured. Data were nalysed by employing SPSS 21. The PSV and EDV increased from 38 to 139 days of gestation. The PI and RI of blood flow showed a non-significant decrease throughout gestation.